Management Forecast Credibility and Underreaction to News - NG, Jeffrey (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we first document evidence of underreaction to management forecast news. We then hypothesize that the credibility of the forecast influences the magnitude of this underreaction. Relying on evidence that more credible forecasts are associated with a larger reaction in the short window around the management forecasts and a smaller post-management forecast drift in returns, we show that the magnitude of the underreaction is smaller for firms that provide more credible forecasts. Our paper contributes to the literature by providing out-of-sample evidence of the drift in returns documented in the post-earnings-announcement drift literature, with the credibility of the news being one explanation for the phenomenon.